The human use of animals : case studies in ethical choice - Orlans, F. Barbara (OUP E-Books., 1998)
This volume of case studies on animal ethics deals with important social controversies involving the human use of animals and analyzes the moral issues involved. An introduction to ethical theory provides a framework to the 16 original case studies, which include the use of animals in research, testing and education, as food, as companion animals, and in religious rites.; The book is intended for bioethics courses and animal career staff.